Cognitive and Brain Structural Changes in a Lung Cancer Population. Issue 1 (January 2015) - Simó, Marta; Root, James C.; Vaquero, Lucía; Ripollés, Pablo; Jové, Josep; Ahles, Tim; Navarro, Arturo; Cardenal, Felipe; Bruna, Jordi; Rodríguez-Fornells, Antoni
Abstract : Introduction: No study has examined structural brain changes specifically associated with chemotherapy in a lung cancer population. The aim of this cross-sectional study was to assess differences in brain structure between small-cell lung cancer patients (C+) following chemotherapy, non–small-cell lung cancer patients (C−) before chemotherapy and healthy controls (HC). Methods: Twenty-eight small-cell lung cancer patients underwent a neuropsychological assessment and a structural magnetic resonance imaging, including T1-weighted and diffusion tensor imaging to examine gray matter density and white matter (WM) integrity, respectively, 1 month following completion of platinum-based chemotherapy. This group was compared with 20 age and education-matched non–small-cell lung cancer patients before receiving chemotherapy and 20 HC. Results: Both C+ and C− groups exhibited cognitive impairment compared with the HC group. The C+ group performed significantly worse than HC in verbal fluency and visuospatial subtests; C− performed significantly worse than both C+ and HC in verbal memory. Voxel-based morphometry analysis revealed lower gray matter density in the insula and parahippocampal gyrus bilaterally, and left anterior cingulate cortex in C+ compared with HC. Diffusion tensor imaging indices showed focal decreased WM integrity in left cingulum and bilateral inferior longitudinal fasciculus in the C+ group and more widespread decreased integrity in the C− group compared with the HC group. Conclusion: This study demonstrates that lung cancer patients exhibit cognitive impairment before and after chemotherapy. Before the treatment, C− showed verbal memory deficits as well as a widespread WM damage. Following treatment, the C+ group performed exhibited lower visuospatial and verbal fluency abilities, together with structural gray matter and WM differences in bilateral regions integrating the paralimbic system.